Interaction of Musicianship and Aging: A Comparison of Cortical Auditory Evoked Potentials - Jennifer L. O’Brien; Dee A. Nikjeh; Jennifer J. Lister (Behavioural Neurology)
Objective. The goal of this study was to begin to explore whether the beneficial auditory neural effects of early music training persist throughout life and influence age-related changes in neurophysiological processing of sound. Design. Cortical auditory evoked potentials (CAEPs) elicited by harmonic tone complexes were examined, including P1-N1-P2, mismatch negativity (MMN), and P3a. Study Sample. Data from older adult musicians (n=8) and nonmusicians (n=8) (ages 55–70 years) were compared to previous data from young adult musicians (n=40) and nonmusicians (n=20) (ages 18–33 years). Results. P1-N1-P2 amplitudes and latencies did not differ between older adult musicians and nonmusicians; however, MMN and P3a latencies for harmonic tone deviances were earlier for older musicians than older nonmusicians. Comparisons of P1-N1-P2, MMN, and P3a components between older and young adult musicians and nonmusicians suggest that P1 and P2 latencies are significantly affected by age, but not musicianship, while MMN and P3a appear to be more sensitive to effects of musicianship than aging. Conclusions. Findings support beneficial influences of musicianship on central auditory function and suggest a positive interaction between aging and musicianship on the auditory neural system.